2019
DOI: 10.1142/s2010132519500123
|View full text |Cite
|
Sign up to set email alerts
|

A Totally Heat-Driven Refrigeration System Using Low-Temperature Heat Sources for Low-Temperature Applications

Abstract: In the present study, a totally heat-driven refrigeration system is proposed and thermodynamically analyzed. This system uses a low-temperature heat source such as geothermal energy or solar energy to produce cooling at freezing temperatures. The proposed system comprises a Rankine cycle (RC) and a hybrid GAX (HGAX) refrigeration cycle, in which the RC provides the power requirement of the HGAX cycle. An ammonia–water mixture is used in both RC and HGAX cycles as the working fluid. A comparative study is condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The simulated results suggested that it was acceptable and effective to place the compressors between heat exchangers, as the coefficients of performance (COP) and the driving temperature of the hybrid systems improved compared with the original system. Seyfouri et al [6] proposed a compressor-assisted hybrid generator absorber heat exchange (GAX) refrigeration system powered by a built-in Rankine cycle to produce cooling below freezing temperatures (as low as −50 • C), for which the heat source temperature was 133.5 • C. Through a parametric study, the optimal operating conditions of the system were obtained. The performance was also enhanced, e.g., COP increased with the rise in the compressor discharge pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The simulated results suggested that it was acceptable and effective to place the compressors between heat exchangers, as the coefficients of performance (COP) and the driving temperature of the hybrid systems improved compared with the original system. Seyfouri et al [6] proposed a compressor-assisted hybrid generator absorber heat exchange (GAX) refrigeration system powered by a built-in Rankine cycle to produce cooling below freezing temperatures (as low as −50 • C), for which the heat source temperature was 133.5 • C. Through a parametric study, the optimal operating conditions of the system were obtained. The performance was also enhanced, e.g., COP increased with the rise in the compressor discharge pressure.…”
Section: Introductionmentioning
confidence: 99%